REFLEKSI KONFLIK ANTARA ULAMA DAN UMARA PADA ABAD KE-19M; TELAAH ATAS NASKAH SIRAJUDDIN - Fakhriati, Fakhriati (P2KK LIPI, 2015)
Historically, Acehnese almost constantly struggled with conflicts. It is recorded that between ulamas (Sufi and Syar’i’s ulamas) had often in disagreement among themselves. The conflict also occured between ulamas and uleebalangs or umara. Not only that, conflict that led people to defend their religion and the nation cannot be avoided when the colonizers tried to enter and dominate Aceh. In this situation, the role of ulamas cannot be denied at all. They took important position as catalysts and mobilizers in the struggle against the colonizers. This information is not only obtained from secondary sources, but also from those directly involved in the conflict. Manuscript of Sirajuddin written by Teungku Muhammad Ali Pulo Pueb, an ulama came from Pidie, Aceh and lived in the 19th century, contains historical facts about several conflicts in Aceh. This Acehnese manuscript would be an interesting subject of study about several conflicts in Aceh because on the one hand the author discussed about Sufi teaching, and on the other, he illustrated the reality of conflict that occurred at that time. Comparison on how other two ulamas, Fakih Jalaluddin and Teungku Khatib Langgien, dealt with the conflict is also discussed in this article in order to understand to what extent of their defends, speaking up for religion, looking after their nation, and also involved in the conflict growth in Colonial era. Keywords: conflict, ulama, umara, manuscript, sufism